Artificial Neural Networks - ICANN 2009 19th International Conference, Limassol, Cyprus, September 14-17, 2009, Proceedings, Part I - Alippi, Cesare; Polycarpou, Marios M.; Panayiotou, Christos; Ellinas, Georgios (Theoretical Computer Science and General Issues,, 2009)
This two volume set LNCS 5768 and LNCS 5769 constitutes the refereed proceedings of the 19th International Conference on Artificial Neural Networks, ICANN 2009, held in Limassol, Cyprus, in September 2009. The 200 revised full papers presented were carefully reviewed and selected from more than 300 submissions. The first volume is divided in topical sections on learning algorithms; computational neuroscience; hardware implementations and embedded systems; self organization; intelligent control and adaptive systems; neural and hybrid architectures; support vector machine; and recurrent neural network.